Characterization of Low-Molecular-Weight Heparins by Strong Anion-Exchange Chromatography - Sadowski, Radosław; Gadzała-Kopciuch, Renata; Kowalkowski, Tomasz; Widomski, Paweł; Jujeczka, Ludwik; Buszewski, Bogusław (Journal of AOAC International, 2017)
Currently, detailed structural characterization of low-molecular-weight heparin (LMWH) products is an analytical subject of great interest. In this work, we carried out a comprehensive structural analysis of LMWHs and applied a modified pharmacopeial method, as well as methods developed by other researchers, to the analysis of novel biosimilar LMWH products; and, for the first time, compared the qualitative and quantitative composition of commercially available drugs (enoxaparin, nadroparin, and dalteparin). For this purpose, we used strong anion-exchange (SAX) chromatography with spectrophotometric detection because this method is more helpful, easier, and faster than other separation techniques for the detailed disaccharide analysis of new LMWH drugs. In addition, we subjected the obtained results to statistical analysis (factor analysis, t-test, and Newman–Keuls post hoc test).